2020
DOI: 10.1155/2020/4513824
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Physical and Rheological Properties of Rejuvenated Styrene‐Butadiene‐Styrene‐Modified Asphalt Binders

Abstract: To evaluate the physical and rheological properties of rejuvenated styrene-butadiene-styrene-modified asphalt (SBSMA) binders designed for rapid in-place pavement recycling, an aged SBSMA binder was rejuvenated with three rejuvenators (i.e., Types I, II, and III) in different dosages. The physical properties of rejuvenated SBSMA were obtained to determine the optimal type and dosage of rejuvenators for the first and second rejuvenation. Performance grade (PG) tests, multiple stress creep recovery (MSCR) tests,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The m-controlled binders failed the m-value threshold of 0.3 at a temperature warmer than the stiffness temperature [31]. It was found that the m-controlled binders exhibited lower thermal stress resistance [32,33].…”
Section: Relationship Between δT C and Abr Percentagementioning
confidence: 99%
“…The m-controlled binders failed the m-value threshold of 0.3 at a temperature warmer than the stiffness temperature [31]. It was found that the m-controlled binders exhibited lower thermal stress resistance [32,33].…”
Section: Relationship Between δT C and Abr Percentagementioning
confidence: 99%
“…The rejuvenation of aged SBSMA and reuse of asphalt mixtures reduces the environmental impacts, such as land occupation and consumption of nonrenewable resources [4]. Rapid in-place pavement recycling at an appropriate time is a very promising technology for preventive maintenance, and has an advantage of time-and cost-efficiency [26]. However, one cycle of rejuvenation has become inadequate to meet the current environmental and traffic demands.…”
Section: Of 19mentioning
confidence: 99%
“…The third aged asphalt-binder and the third rejuvenated asphalt-binder were obtained by the same method. Figure 2 For the purpose of investigating the influence of multiple aging and rejuvenation cycles on the SBSMA in the field, 6%, 10%, and 14% by weight (wt%) of the asphalt-binder were selected as the rationale dosage of the rejuvenator for the first, second, and third rejuvenation, respectively, in accordance with previous research studies [26]. The first aged SBSMA was heated to 140~160 • C for melting and blended with three rejuvenators for 30 min to prepare the first rejuvenated SBSMA.…”
Section: Experimental Design Planmentioning
confidence: 99%